Minoes, Minnie, Minu en andere katse streken. De internationale receptie van Annie M.G. Schmidts Minoes - Barbara Kalla, Irena; Van Coillie, Jan (Lage Landen Studies, 2017)
This volume focuses on the international reception of Annie M.G. Schmidt's Minoes, the most translated Dutch children's book. The authors investigate the reception and adaptations in the Netherlands and Flanders, the French translation and Canadian retranslation, the Hungarian translation and theatrical adaptation, and the Swedish, Russian, Polish and African reception.